The Effect of Achievement Motivation on Academic Flow: A Simple Regression Analysis of Vocational High School Students in Central Java - Agustin Andhika Putri; Elyssabet Yeni Purwaningsih; Yefta Irene Melsandi; Eustakia Elvira Ayu Rosari; Esra Ardini; V. Rekyanworo Arum Damayanti (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – The problem of low achievement motivation among vocational high school students has implications for low learning engagement and academic flow. Therefore, this study aims to examine the effect of achievement motivation on the academic flow of students at Vocational School X. Methods – The population in this study consisted of 182 students in grade XI at Vocational School X. Data analysis used simple linear regression analysis. The data collection method used was an achievement motivation questionnaire, and the academic flow variable was measured using the Flow Inventory for Students scale. The research results were processed using the JASP program. Findings – Based on the descriptive statistics, 135 students were at a moderate level of achievement motivation, 113 students were at a moderate level of academic flow, and 37 students were at a high level of academic flow. Furthermore, based on the regression analysis results, a p-value of 0.001 and R2 = 0.099 were obtained. This means that if the p-value is < 0.05, it can be concluded that achievement motivation has an effect on students' academic flow. However, the contribution of achievement motivation is only 9.9%, with the remainder explained by other factors not examined in this study.Research Implications – The findings imply that efforts to enhance students’ academic flow should not focus solely on achievement motivation, as academic flow is influenced by multiple factors. Future studies are encouraged to examine additional predictors, such as self-efficacy, social support, and learning environment, to develop a more comprehensive understanding of academic flow among vocational high school students.